High Waves, Quiet Backwaters. (1st October 2016) - Shickarev, Sergei
Abstract : The article considers the new generation of speculative fiction writers in Russia, who started publishing in the late 2000s and early 2010s. Central among them is a loosely connected group of authors known collectively as the Color Wave. Their primary focus is on "inner space" and emotional processes, while they usually avoid social aspects and problems of the real world. The article describes the genesis and conceptual framework of the Color Wave, listing the most prominent authors and works associated with the movement. Other significant authors of the same generation are discussed as well.